Role of diffusion-weighted imaging in monitoring treatment response following high-intensity focused ultrasound ablation of recurrent sacral chordoma - Chetan, M; Lyon, P; Wu, F; Phillips, R; Cranston, D; Gillies, M; Bojanic, S (Elsevier, 2019)
Chordoma is the most common malignant tumor of the sacrum and is associated with significant neurologic morbidity. Local recurrence is very common, and the long-term prognosis is poor. High-intensity focused ultrasound (HIFU) is a noninvasive and nonionising ablative therapy that has been successful in treating other tumor types and is being evaluated as a new therapy for sacral chordoma. Contrast-enhanced magnetic resonance imaging is typically used to evaluate tumor perfusion following HIFU; however, its utility is limited in poorly perfused tumors. Diffusion-weighted imaging (DWI) provides tissue contrast based on differences in the diffusion of extracellular water without using gadolinium-based contrast agents. We present novel DWI findings following a planned partial HIFU ablation of a large sacral chordoma which had recurred after radiotherapy. Following HIFU, the treated tumor volume demonstrated loss of restriction on DWI correlating with photopenia on positron emission tomography. This suggests successful ablation and tumor necrosis. This novel finding may provide guidance for sequence selection when evaluating HIFU therapy for sacral chordoma and other tumor types for which contrast-enhanced magnetic resonance imaging may have limited utility.